Maternal effects shape the seed mycobiome in Quercus petraea. Issue 4 (23rd January 2021) - Fort, Tania; Pauvert, Charlie; Zanne, Amy E.; Ovaskainen, Otso; Caignard, Thomas; Barret, Matthieu; Compant, Stéphane; Hampe, Arndt; Delzon, Sylvain; Vacher, Corinne
Summary: The tree seed mycobiome has received little attention despite its potential role in forest regeneration and health. The aim of the present study was to analyze the processes shaping the composition of seed fungal communities in natural forests as seeds transition from the mother plant to the ground for establishment. We used metabarcoding approaches and confocal microscopy to analyze the fungal communities of seeds collected in the canopy and on the ground in four natural populations of sessile oak ( Quercus petraea ). Ecological processes shaping the seed mycobiome were inferred using joint species distribution models. Fungi were present in seed internal tissues, including the embryo. The seed mycobiome differed among oak populations and trees within the same population. Its composition was largely influenced by the mother, with weak significant environmental influences. The models also revealed several probable interactions among fungal pathogens and mycoparasites. Our results demonstrate that maternal effects, environmental filtering and biotic interactions all shape the seed mycobiome of sessile oak. They provide a starting point for future research aimed at understanding how maternal genes and environments interact to control the vertical transmission of fungal species that could then influence seed dispersal and germination, and seedling recruitment. Abstract : See also the Commentary on this article by U'Ren & Zimmerman, 230 : 1293–1295 .